First isolation and molecular characterization of Suid herpesvirus type 1 from a domestic dog in Argentina - Maria Soledad Serena; Germán Ernesto Metz; Maria Ines Lozada; Carolina Gabriela Aspitia; Edgardo Héctor Nicolino; Claudio Luis Pidone; Melisa Fossaroli; Agustin Balsalobre; Maria Alejandra Quiroga; Maria Gabriela Echeverria (Open Veterinary Journal, 2018)
Since Aujeszky`s disease (pseudorabies), which is caused by Suid herpesvirus type 1 (SuHV-1), was first notified in Argentina in 1978, many SuHV-1 strains have been isolated from swine. However, this disease can affect other vertebrates, such as dogs (secondary hosts), and lead to fatal neurological disease. The objective of the current work is to report the first isolation and molecular characterization of SuHV-1 from a dead domestic dog from Santa Fe Province (Argentina), which had had nervous signs compatible with pseudorabies. Samples of brain and trigeminal ganglia from this dog were obtained and fixed in formol for histopathology, and virology studies were conducted after cell disruption. Supernatants of both samples were inoculated onto RK13 cells and, after 72 h, DNA was extracted with phenol-chloroform. Purified DNA was cut with a restriction enzyme and subjected to agarose gel and an aliquot was used to amplify the gD and gC genes by PCR. The gC sequence was compared with other public sequences. The strain isolated from the dog was similar to other Argentinean swine strains.